2015
DOI: 10.1002/asia.201501203
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Hierarchical TiO2/Fe2O3 Composite Membrane with High Separation Efficiency for Surfactant‐Stabilized Oil‐Water Emulsions

Abstract: Globally, efficient oil-water separation for surfactant-stabilized oil-water emulsions has been in urgent demand. The current options available for separation are neither sustainable nor resistant to fouling. Herein, we introduce a hierarchically nanostructured TiO2/Fe2O3 composite membrane, which is capable of separating surfactant-stabilized oil-water emulsions with high separation efficiency. The high oil rejection rate is contributed by the acquisition of an interconnected delicate network and underwater s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The presence of nanocomposites can be beneficial for the flux and anti‐fouling properties until an optimal amount from which it can start to jeopardize membrane performance, for example, by reducing hydrophilicity, enlarging pore size, reducing rejection rate, increasing fouling layer, reducing flux, etc 106,197,198,200 Membrane regeneration can be almost complete as it was observed in most of the cited studies, because flux recovery was often ~100%, even after several cycles 155,191,199,200,202–204 Photocatalytic properties are often characterized by dye (e.g., methylene blue) decomposition, due to its relatively fast degradation and the relative ease of the analytic method, as it can be measured by a spectrophotometer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of nanocomposites can be beneficial for the flux and anti‐fouling properties until an optimal amount from which it can start to jeopardize membrane performance, for example, by reducing hydrophilicity, enlarging pore size, reducing rejection rate, increasing fouling layer, reducing flux, etc 106,197,198,200 Membrane regeneration can be almost complete as it was observed in most of the cited studies, because flux recovery was often ~100%, even after several cycles 155,191,199,200,202–204 Photocatalytic properties are often characterized by dye (e.g., methylene blue) decomposition, due to its relatively fast degradation and the relative ease of the analytic method, as it can be measured by a spectrophotometer.…”
Section: Discussionmentioning
confidence: 99%
“…Both membrane hydrophilicity and membrane oleophobicity have to be studied in depth in order to (a) prevent the permeation of oil droplets, (b) selectively separate water from the oil‐water mixtures, and (c) minimize the adhesion of the oil droplets 133,208 Most of the studies investigated photocatalysis followed by membrane filtration 173,197 or membrane filtration followed by photocatalytic cleaning 106,155,191,198–200,206,207 . There is a lack of research that combines decomposition and self‐cleaning simultaneously. The membrane stability—both UV, oxidation, and adherence—has to be studied in situ without making generalizations about the used material 115,138,154 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes with selective wettability have been incorporated with photocatalytic materials (e.g., TiO 2 6 , 33 , N-TiO 2 34 , α-Fe 2 O 3 16 , 35 , Fe 3 O 4 36 , WO 3 37 , ZnO 38 , BiVO 4 7 , α-FeOOH 39 , MoO 3 40 , Co 3 O 4 41 , Gd 2 ZnMnO 6 /ZnO 42 ) that can degrade the organic substances deposited on the surface upon light illumination. These membranes have demonstrated that they can oxidize (or reduce) the organic substances either dissolved in a liquid (e.g., water) or adsorbed on the membrane surface when irradiated by light with an energy higher than their bandgap energy 43 , 44 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, such membranes with selective wettability (i.e., hydrophilic and in air or underwater oleophobic) have been incorporated with a photocatalytic semiconductor (e.g., TiO 2 , [ 26 ] α‐Fe 2 O 3 , [ 27 ] WO 3 , [ 28 ] BiVO 4 , [ 29 ] β‐FeOOH, [ 30 ] g‐C 3 N 4 , [ 31 ] and CuWO 4 @Cu 2 O [ 32 ] ), which allows for catalytic degradation of the organic contaminants dissolved in the water‐rich permeate upon irradiation of light. Photocatalytic materials generate electron hole (e − ‐h + ) pairs upon irradiation of light with an energy greater than their bandgap energy ( E g ).…”
Section: Introductionmentioning
confidence: 99%